Bone Eosinophilic Granuloma - Cabieses Molina, Fernando (1953)
Four cases of monostotic eosinophilic granuloma are presented. Three of them located in the skull and one located in a vertebra. The relationship between this entity and the disease, Hand-Schuller-Christian and Letterer-Siwe is emphasized, highlighting the mild monostotic eosinophilic granuloma.